Penciptaan Busana dengan Sumber Ide Rumah Adat Suku Tengger - Susi Gomes; Inty Nahari; Imami Arum Tri Rahayu; Lutfiyah Hidayah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The creation of this work is based on the type of Practice-Ed Research approach carried out through a study of fashion design practices with a focus on "Creation of Fashion with the Source of Ideas for the Tengger Tribe's Traditional House". This study of the creation practice aims to convey ideas and concepts for fashion design as well as methods and techniques for making clothes and can increase knowledge and skills in making clothes. This work is based on the source of ideas for the Tengger tribe's traditional house whose design and shape have uniqueness from other traditional houses besides that the Tengger tribe's traditional house is a traditional house that is now rarely inhabited by the community, especially the community around Bromo, namely the Tengger tribe who choose to build more modern houses and are also still very minimal to be used as a source of ideas in making clothes. To achieve this goal, the method of making this work of practice, through four stages, namely; exploration, design, embodiment and presentation, by applying embroidery decorative motifs from the source of ideas for traditional houses to making clothes. The results of this creation process are in the form of 3 pieces of clothing presented in the form of several on-events, namely fitting 1, fitting 2, grand jury, grand show or fashion show held in front of the rectorate building of the state university of Surabaya, with offline presentation techniques or coming directly and online or virtual exhibition.